(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
The article describes the phases of application of combat techniques in skilled wrestlers and the determination of the level of development of hand strength and types of force in their execution. It is assumed that the results of such an assessment of strength and types of force can serve to increase the effectiveness of their establishment and improvement during training.